Comunicação e religião : um estudo comparado sobre terrorismo no L’osservatore romano e no Al-Azhar observer - Garibaldi, Lorena Barros (2018)
Terrorist attacks have been extensively held by the international media in the last years. With religious and the political traces, this concern is also subject in the segmented media. The present study aims to analyze the coverage performed by the Vatican website, L'Osservatore Romano (http://www.osservatoreromano.va/), as well as by the Al-Azhar Observatory website (http://www.azhar.eg/observer-en), an Islamic of Sunni doctrine digital media belonging to the homonymous university, on the subject of terrorism. To this end, this study seeks to ascertain the frameworks made through the speeches used by the mentioned sites. The present research employed, mainly, the theoretical concepts of Huntington (2010), Demant (2018), Wainberg (2005) and Castells (2015). The corpus of this study was investigated by applying the French Speech Analysis (TA) and, as a tool for analyzing, the software Linguistic Research and Word Count - LIWC.